(untitled) (Revista Sistemas de Producción Agroecológicos, 2011)
In Chipaque, Cundinamarca, Colombia, dairy farms have dual-purpose cattle, the breeds are selected, being the predominant Norman crosses with Holstein and Creole animals, milking the presence of the calf. It should be noted that the marketing of milk continues to be done regardless of the quality of the product, The milk buyers pay only for volume, which does not encourage an effort by the producer to improve physicochemical and microbiological quality of this food, based on foregoing, the University of the Llanos, through its social programs and a student proposed to carry out a diagnosis which determined the quality of milk, and the characteristics of marketing in Chipaque, for which identified the parameters of milk constituents and analyze marketing. For the study surveys were applied to producers and marketers of milk, the results were that Chipaque has about 2.300 lactating cows involved in the commercial production of milk under the dual-purpose system and 99 cows for intensive dairy system. The daily production of milk is approximately 13,800 liters and 6 liters daily cow /per/ day, production and increases in the rainy season. The milk is sold at 100% as raw milk bound of 65% for dairy factories, 30% with intermediate and 5% sold by the producer. Although they have a significant percentage (7%) of Holstein cows given the management system is the same dual purpose, milking and calf rearing side and males and females with weaning between 8-13 months of age (97 %), only 3% of producers weaned the first day. It is important to emphasize the physical and chemical quality of milk which gives total solids 12.77% and 87.23% water of constitution.